2011
DOI: 10.1242/jcs.081216
|View full text |Cite
|
Sign up to set email alerts
|

A mitotic role for Mad1 beyond the spindle checkpoint

Abstract: SummaryUnattached kinetochores generate an anaphase inhibitor, through the spindle assembly checkpoint (SAC), that allows cells more time to establish proper kinetochore-microtubule (K-MT) linkages and thus avoid aneuploidy. Mad1 is the receptor for Mad2 at kinetochores, where it catalyzes the formation of Mad2-Cdc20 complexes, an essential part of the anaphase inhibitor, but whether it has any other mitotic function is unknown. We have generated a mad1-null mutation in Drosophila. This mutant is SAC defective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 51 publications
6
43
0
Order By: Relevance
“…As is the case for Mad1-null mutants (Emre et al, 2011), these lagging chromatids were in most cases correctly segregated, despite their delay in migration (given that overall aneuploidy levels are low). In several cases, the lagging chromatids appeared to be attached to spindle fibers emanating from both poles (merotelic attachment), which is also a feature associated with mitosis in Mad1-null mutants (Emre et al, 2011).…”
Section: Research Articlementioning
confidence: 76%
See 2 more Smart Citations
“…As is the case for Mad1-null mutants (Emre et al, 2011), these lagging chromatids were in most cases correctly segregated, despite their delay in migration (given that overall aneuploidy levels are low). In several cases, the lagging chromatids appeared to be attached to spindle fibers emanating from both poles (merotelic attachment), which is also a feature associated with mitosis in Mad1-null mutants (Emre et al, 2011).…”
Section: Research Articlementioning
confidence: 76%
“…3F), however, showed that there was an elevated frequency of anaphases in which some kinetochores migrated poleward more slowly than the others. Indeed, the fraction of anaphases with at least one lagging kinetochore was nearly as high in rod Z3 as in rod or Mad1-null mutants (Emre et al, 2011), although only rarely was more than one kinetochore involved (Table 3). As is the case for Mad1-null mutants (Emre et al, 2011), these lagging chromatids were in most cases correctly segregated, despite their delay in migration (given that overall aneuploidy levels are low).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In fly, mad1-null mutant cells show higher rate of lagging chromosomes in anaphase compared to mad2-null mutant cells. 19 This indicates Mad1 has a role in chromosome bi-orientation beyond the SAC. Interestingly, this role depends on Mad2-interacting motif of Mad1, although mad2-null mutant cells undergo normal anaphase.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this role depends on Mad2-interacting motif of Mad1, although mad2-null mutant cells undergo normal anaphase. 19 Molecular mechanisms how Mad1 promotes chromosome bi-orientation remain elusive. Similarly, in fission yeast, mad1D cells show higher sensitivity to spindle drugs compared to mad2D or mad3D cells.…”
Section: Introductionmentioning
confidence: 99%